IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AND PRUDENTIAL PRINCIPLES (PRUDENTIAL BANKING REGULATIONS) IN BANKING - Erikson Sihotang (Warmadewa Press, 2021)
Banks are required to improve bank health in accordance with the provisions of the aspects of capital adequacy, asset quality, management quality, liquidity, profitability, solvency, and other aspects related to bank business, and are required to conduct business activities in accordance with the principles of prudence. The principle of trust is the main, basic, and most important principle of banking activities. Banks are institutions based on trust by taking advantage of fiduciary obligations from customers to banks in the form of trust in customer data and money from customers. The bank has a function as an intermediary institution that assists in the smooth operation of the payment system, as well as as an institution that becomes a vehicle for Government Policy policies, namely monetary policy. The application of the precautionary principle has a wide scope, not only in relation to the process of providing credit or corporate financing by banking financial institutions as stated in the Banking Act but also all aspects of banking company services. The aim of this research is to know the governance of the bank in order to prevent public doubts about the financial system of the bank.